Orkes Gumarang: Pelopor Musik Minang Modern Tahun 1953-1980 - Yori, Dean Stales (Pendidikan Sejarah, 2014)
This paper discusses the gait Gumarang Orchestra as the pioneer of Modern Music Minang Year 1953-1980. The problem of this research is: How Background formation Gumarang Orchestra, how existence Gumarang Orchestra in the years 1953-1980, and how Minang community responses to the works of Gumarang Orchestra. The method used in this research is a method composed of heuristic history, criticism, interpretation and historiography. The survey results revealed that the establishment originated from the desire Gumarang Orchestra personnel who wish to pursue gait Penghibur Hati Orchestra and Orchestra disbanded Gumarang formed in 1953 consisting of 7 members. Orchestra Gumarang existed for 27 years and stopped in 1980. During its existence Orchestra Gumarang experienced personnel changes and leadership. Throughout its existence Orchestra Gumarang produce songs that are much favored by the public as a phenomenal song Ajam Den Lapeh, Laruik Sanjo and others. But not many people know about Gumarang orchestra personnel, except those involved in the world of music. Community only know the songs sung by the orchestra Gumarang